Diversity and stability of fishes (Teleostei) in a temporary river of the Brazilian semiarid region - Elvio S.F. Medeiros; Leonardo Maltchik (Iheringia: Série Zoologia, 2001)
The effects of hydrological disturbances by flooding and drought on the diversity and stability in a temporary river fish community in the Brazilian semiarid region were analyzed over the 1996 hydrological cycle. Twelve collections of fishes were made during the wet and dry phases, and 789 individuals of 16 species were collected. Diversity was measured using Simpson's Index (S) and community stability was analyzed by the variation in abundance using Kendall's W concordance test. Fish diversity in the Taperoá river was subjected to hydrological disturbances by flooding and drought. During the wet phase the diversity was higher (S = 0.855) than during the dry phase (S = 0.771). The community was considered stable during the whole annual hydrological cycle (W = 0.418 p < 0.001), but a higher stability in the community was found during the dry phase. During the dry phase the number of dominant species was smaller than during the wet phase.